Investment Earnings as a Countercyclical Tool: Evidence from U.S. State Governments - Kim, Sungchan; Park, Soyoung (International Journal of Economics and Financial Issues, 2017)
Budget stabilization funds (BSFs) play an important role as a safety device for countercyclical fiscal capacity (CCFC) in the United States. However, while BSFs take on a kind of allowance for a contingent budget deficit, state governments can't expect high return on the money because the BSFs should be used immediately. They can alternatively provide profits from short-term investment earnings with safety and liquidity. Thus, the purpose of this study is to examine whether investment earnings decrease the volatility of total general fund expenditures (GFEs) and improve budget performance in state government. By using OLS regression models with a paneled data set ranging from 2002 to 2013, this study concludes that investment earnings increase the volatility of GFEs, while the generally accepted countercyclical tools such as BSFs and UUBs reduce it. In addition, it also finds that investment earnings are a source of better performance in state government. Keywords: investment earning, budget performance, countercyclical fiscal capacity (CCFC), budget stabilization fund (BSF) JEL Classifications: E6, H6